2019
DOI: 10.3389/fmicb.2019.01039
|View full text |Cite
|
Sign up to set email alerts
|

The MarR-Type Regulator MalR Is Involved in Stress-Responsive Cell Envelope Remodeling in Corynebacterium glutamicum

Abstract: It is the enormous adaptive capacity of microorganisms, which is key to their competitive success in nature, but also challenges antibiotic treatment of human diseases. To deal with a diverse set of stresses, bacteria are able to reprogram gene expression using a wide variety of transcription factors. Here, we focused on the MarR-type regulator MalR conserved in the Corynebacterineae , including the prominent pathogens Corynebacterium diphtheriae and My… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 81 publications
(101 reference statements)
0
10
0
1
Order By: Relevance
“…Notably, the lipid profile of N-MVs fraction was different from those of M-MVs, P-MVs, and B-MVs fractions ( Figures S16–S18 ), and the addition of biotin to the culture failed to decrease N-MV release ( Figure S19 ), indicating that N-MVs were formed through a mechanism different than that of B-MVs. The drastic changes in the cellular membrane lipid compositions among the growth conditions, especially MMC and penicillin G conditions, suggest stress-responsive membrane remodeling caused by MalR ( Hünnefeld et al., 2019 ), a MarR-type regulator that has been proposed to be involved in adaptation of C. glutamicum cells to DNA stress and inhibition of cell wall biosynthesis. The previous study ( Hünnefeld et al., 2019 ) has identified binding sites of MalR in C. glutamicum genomes and revealed that MalR regulates expressions of several genes, such as ipsA and oppA , involved in cell membrane remodeling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the lipid profile of N-MVs fraction was different from those of M-MVs, P-MVs, and B-MVs fractions ( Figures S16–S18 ), and the addition of biotin to the culture failed to decrease N-MV release ( Figure S19 ), indicating that N-MVs were formed through a mechanism different than that of B-MVs. The drastic changes in the cellular membrane lipid compositions among the growth conditions, especially MMC and penicillin G conditions, suggest stress-responsive membrane remodeling caused by MalR ( Hünnefeld et al., 2019 ), a MarR-type regulator that has been proposed to be involved in adaptation of C. glutamicum cells to DNA stress and inhibition of cell wall biosynthesis. The previous study ( Hünnefeld et al., 2019 ) has identified binding sites of MalR in C. glutamicum genomes and revealed that MalR regulates expressions of several genes, such as ipsA and oppA , involved in cell membrane remodeling.…”
Section: Resultsmentioning
confidence: 99%
“…The drastic changes in the cellular membrane lipid compositions among the growth conditions, especially MMC and penicillin G conditions, suggest stress-responsive membrane remodeling caused by MalR ( Hünnefeld et al., 2019 ), a MarR-type regulator that has been proposed to be involved in adaptation of C. glutamicum cells to DNA stress and inhibition of cell wall biosynthesis. The previous study ( Hünnefeld et al., 2019 ) has identified binding sites of MalR in C. glutamicum genomes and revealed that MalR regulates expressions of several genes, such as ipsA and oppA , involved in cell membrane remodeling. Positive and negative regulation of these genes by MalR may result in modulation of lipid composition of C. glutamicum membranes upon the cell envelope and DNA stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found a SNP in the intergenic region between cg3314 and cg3315, four nucleotides upstream from the translation start of MalR ( malR , cg3315). This protein has been originally identified as repressor of the malE gene in the study of Krause et al ( 2012 ) and was recently reported to bind to several other loci (Hünnefeld et al, 2019 ). Since the mutation occurred outside the coding sequence of this regulator, only expression changes of the gene are able to affect metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In motif A’, more positions tend to be conserved, and the partial palindromic structure within the first 12 base pairs positions of the motif is even more evident, as presented by underlined positions marked by // indicating the plane of symmetry in the consensus sequence TT T CA G//T TG G AA GCA presented in Figure 4 F. The identified motif resembles the MarR-type regulator SlyA binding site TTAGCAAGCTAA [ 43 ]. It is worth mentioning that also non-perfectly palindromic sequence motifs bound by MarR-type transcriptional regulators were found e.g., for MalR from Corynebacterium glutamicum , consensus TTnAAnnnTCAA [ 61 ]; HpaR from Xanthomonas campestris —consensus [G/T]CAACAATT[C/T]TTG [ 62 ] or CosR from Vibrio parahaemolyticus —consensus TTTGA-NN-TCTAA [ 63 ].…”
Section: Discussionmentioning
confidence: 99%